1999
DOI: 10.1007/bf02562293
|View full text |Cite
|
Sign up to set email alerts
|

The double bond in unsaturated fatty acids is the necessary and sufficient requirement for the inhibition of expression of endothelial leukocyte adhesion molecules through interference with nuclear factor‐κB activation

Abstract: Conclusions These results indicate that the single double bond present in oleic acid is a necessary and sufficient requirement for FA inhibition of endothelial activation. Since this occurred independent of the stimuli used and was present also with PMA, bypassing membrane receptors, these results point to an interference with a common signal transduction pathway for cytokine signaling. These results are accounted for by an inhibition of NF‐χB activation, here demonstrated at the same concentrations required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In one such study, LA in combination with IL-1α was found to decrease the expression of adhesion molecules ICAM-1, VCAM-1, and E-selectin from endothelial cells when compared with IL-1α treatment alone, with decreased monocyte adherence as a fi nal end point [38]. In support of the anti-infl ammatory effects reported for LA, other investigators have found that endothelial cell activation decreases as the level of unsaturation increases [39,40]. However, most of these studies compare the cellular activation of LA in combination with a proinfl ammatory stimulus to the effects of the stimulus alone, whereas the effects of LA are still greater than no treatment.…”
Section: Effects Of Fatty Acids On Vascular Infl Ammationmentioning
confidence: 81%
“…In one such study, LA in combination with IL-1α was found to decrease the expression of adhesion molecules ICAM-1, VCAM-1, and E-selectin from endothelial cells when compared with IL-1α treatment alone, with decreased monocyte adherence as a fi nal end point [38]. In support of the anti-infl ammatory effects reported for LA, other investigators have found that endothelial cell activation decreases as the level of unsaturation increases [39,40]. However, most of these studies compare the cellular activation of LA in combination with a proinfl ammatory stimulus to the effects of the stimulus alone, whereas the effects of LA are still greater than no treatment.…”
Section: Effects Of Fatty Acids On Vascular Infl Ammationmentioning
confidence: 81%
“…This condition might occur by two mechanisms: reduced enzymatic production of ROS or increased scavenging after their production. It has been suggested that the inhibitory potency of UFAs is directly proportional to their number of double bonds [153,156]. According to this, DHA, with six double bonds, would be six times more potent than oleic acid.…”
Section: Effects Of Oleic Acidmentioning
confidence: 97%
“…Supplementation of endothelial cells with oleic acid in vitro reduces endothelial cell sensitivity to oxidants, creating a reduced pro-oxidant environment as a consequence of reduced intracellular ROS [151,152]. In this environment, oleate reduces the activation and mRNA expression of NFnB and AP-1, thereby interfering with the endothelial expression of adhesion molecules for circulating monocytes and contributing to a direct vascular atheroprotective effect [153][154][155][156]. In addition, cellular treatment with this fatty acid protects endothelial cells against cytokine-induced VCAM-1, ICAM-1 or E-selectin overexpression [147].…”
Section: Effects Of Oleic Acidmentioning
confidence: 99%
“…PUFA. Both teams agreed on the pro-activating effect of saturated fatty acids and the inhibition of endothelial activation by oleic acid, but their opinions diverged with respect to linoleic acid: according to De Caterina and Libby, linoleic acid inhibits endothelial activation solely because of its unsaturation and independently of its nature, 37,38 but this observation opposed that of the pro-activating effect previously demonstrated with this fatty acid. 33,35,39 The latter study suggested a certain speci city regarding the respective roles of n-6 and n-3 PUFA in endothelial dysfunction.…”
Section: Fatty Acids and Adhesion Moleculesmentioning
confidence: 87%